If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7p + 2(-3p + 2) = 4(p + 1) Reorder the terms: -7p + 2(2 + -3p) = 4(p + 1) -7p + (2 * 2 + -3p * 2) = 4(p + 1) -7p + (4 + -6p) = 4(p + 1) Reorder the terms: 4 + -7p + -6p = 4(p + 1) Combine like terms: -7p + -6p = -13p 4 + -13p = 4(p + 1) Reorder the terms: 4 + -13p = 4(1 + p) 4 + -13p = (1 * 4 + p * 4) 4 + -13p = (4 + 4p) Add '-4' to each side of the equation. 4 + -4 + -13p = 4 + -4 + 4p Combine like terms: 4 + -4 = 0 0 + -13p = 4 + -4 + 4p -13p = 4 + -4 + 4p Combine like terms: 4 + -4 = 0 -13p = 0 + 4p -13p = 4p Solving -13p = 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -13p + -4p = 4p + -4p Combine like terms: -13p + -4p = -17p -17p = 4p + -4p Combine like terms: 4p + -4p = 0 -17p = 0 Divide each side by '-17'. p = 0 Simplifying p = 0
| P=8n+4 | | 0.5/2a/3 | | 18=1-8p+1 | | 4+3n-8n=-3n-8+n+6 | | 8+6(6+6m)=116 | | 3h-1=5 | | 18-3n=4n+11 | | 13+8m=7m+14 | | w+15=2 | | 1-7y=2y-14 | | (2x)(x+4)=0 | | 5t+4r+9=0 | | 9+3.5f=11-0.5g | | 36+2y=-4y | | 5x+9-3x=0 | | X^2-4x-k+4=0 | | x+73=4961 | | 29-y=37 | | 5x+9=11x-27 | | (x)(4x+5)=520 | | 2y=-3x+29 | | -7x+9=19-3x | | -2y-3y+9=4-3-y | | 600=300+10c | | X^2-12x+49=22 | | 13y+2=9y+22 | | 97b=2037 | | 14x-9x=7 | | 11n^2=5n^2 | | 16b=128 | | 600=5s+400 | | x-.16x=543.90 |